Associations of Face-to-Face and Instant Messaging Family Communication and Their Contents With Family Wellbeing and Personal Happiness Amidst the COVID-19 Pandemic - Gong, Wei Jie; Sit, Shirley Man Man; Wong, Bonny Yee Man; Wu, Socrates Yong Da; Lai, Agnes Yuen Kwan; Ho, Sai Yin; Wang, Man Ping; Lam, Tai Hing (Frontiers in Psychiatry, 2022)
Background: Both face-to-face and instant messaging (IM) communication are important for families, but face-to-face communication has reduced amidst the COVID-19 pandemic. We examined the use and contents of both communication methods amidst the COVID-19 pandemic, their associations with family wellbeing and personal happiness, and the mediation effects of communication quality. Methods: Under the Hong Kong Jockey Club SMART Family-Link project, this territory-wide self-administered online survey enrolled 4921 Hong Kong Chinese adults in May 2020. Respondents reported (i) any face-to-face or IM communication with family when the COVID-19 pandemic was severe; (ii) contents of family communication that were classified as neutral, positive, supportive, and negative; and (iii) communication quality, family wellbeing, and personal happiness (score 0-10). Associations of family wellbeing and personal happiness with communication methods and contents (no communication excluded) were examined using linear regressions (β), adjusting for each other, sex, age, socioeconomic status, and the number of cohabitants. Mediating effects of communication quality on these associations were examined. Prevalence estimates were weighted by sex, age, and education of the general population. Interactions of methods and contents were examined. Results: Of 4891 included respondents (mean age 43.5 years), 7.1% reported no communication, 12.7% face-to-face communication only, 26.7% IM only, and 53.4% both methods. More respondents reported neutral (83.1-99.3%) than positive (42.1-62.2%), supportive (37.5-54.8%), and negative (10.9-34.5%) contents despite communication methods. Communication quality was higher with both methods than IM only, face-to-face only, and no communication (scores: 6.7 vs 4.5-6.6, all P≤0.02). Better family wellbeing and personal happiness were associated with using IM only (adjusted βs: 0.37 and 0.48) and both methods (0.37 and 0.42) than face-to-face only, and positive (0.62 and 0.74) or supportive (0.45 and 0.46) contents (all P≤0.001). Communication quality mediated 39.4-93.5% of these associations. Communication methods moderated the associations between positive contents and family wellbeing, showing stronger associations of family wellbeing with both methods and face-to-face only than IM only (P for interaction=0.006). Conclusions: We have first shown that, amidst the COVID-19 pandemic, family IM communication and positive and supportive contents may promote family wellbeing and personal happiness. People with no family communication may need assistance.